Komposisi Spesies Ikan Karang Di Perairan Desa Bunutan, Kecamatan Abang, Kabupaten Karangasem, Bali - Dhananjaya, I Gusti Ngurah Agung; Hendrawan, I Gede; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017)DO - 10.24843/jmas.2017.v3.i01.91-98, 2017)
Bunutan village is located in the Abang Subdistrict, Karangasem Regency, Bali. Marines of Bunutan has a coral reef coverage and reef fish under the water. This study aims to determine the species composition of reef fish in marine of Bunutan. The methods used to take reef fish data is Visual Census along 50 meters transect parallel a coastline at a depth of ±5 meters. Result of this study shows thats abudance of reef fish is about 1513 individual from 68 species and 18 family all around transect. The highest abudance derived from Pomacentridae Family with a total 1055 individual from 22 species founded. The composition of species in Bunutan marine site generally in a good condition with high diversity H’ = 3,188418, uniformity is fairly stable with value E = 0,753032 and with the value of dominance C = 0,069245 or nothing of coral reef fish which dominate each other. In terms of role fish in the sea, reef fish in Bunutan marine site have major fish about 92%, target fish 2% and indicator fish 6%. When relating to the condition of coral reefs in the marines of Bunutan, hard coral cover percentage is on 48.5% to 54.5% thats indicates the condition of coral reefs on moderate to good condition. The condition of coral reefs is utilized by reef fish as a place of refuge, feeding or breeding grounds, causing the species composition of reef fish in the marine of Bunutan on relatively good.
Keywords: species composition, reef fish, coral reff, Bunutan